Going (More) Public: Institutional Isomorphism and Ownership Reform among Chinese Firms. (更多的)上市流通：制度同构与中国公司的股权改革. (1st March 2013) - Haveman, Heather A.; Wang, Yongxiang
<x xml:space="preserve">Abstract</x> Abstract Publicly traded Chinese firms recently reformed their ownership structures by converting non‐tradable shares, which constituted two‐thirds of shares outstanding and were held largely by the state, into shares that could trade on domestic exchanges. To facilitate this reform, tradable shareholders were compensated with stock grants from non‐tradable shareholders. Our analysis focuses on the level of compensation, the compensation ratio, the ratio of new tradable shares granted to tradable shares outstanding before the reform. Contrary to the predictions of asset‐pricing models, most firms set the compensation ratio around 0.3. We explain this surprising convergence using institutional theory. In doing so, we analyze the power and interests of all relevant actors – not just owners, but also state regulators, executives, and other agents – and draw on insights from resource‐dependence and agency theories. We find strong evidence of coercive and mimetic isomorphism, but no evidence of normative isomorphism. Because our dependent variable is continuous (a ratio), we are able to show that the mimetic effects we observe cannot be attributed to coercion or norms. Thus, we not only explain an empirical puzzle, we also advance institutional analysis of isomorphism by clearly distinguishing three isomorphic forces that have been conflated in much previous research. 摘要 中国上市公司最近对他们的股权结构进行变革。原先占总股权三分之二比例的非流通股在改革之后将被允许上市流通。为推动改革的顺利进行，非流通股股东根据监管要求，需要支付对价给流通股股东。我们的分析关注于这一对价。有别于经典的资产定价模型，我们发现对价大部分被定在0.3左右，即每10股流通股平均可以从非流通股股东获得3股的补偿。我们利用社会学中的制度理论解释这一奇怪的对价高度聚集现象。为此，我们分析了参与谈判的各方 – 不仅包括股东，还包括政府监管机构等 – 的权力和各自的利益关系；同时，我们还将资源依赖理论以及委托代理理论引入制度理论。初步分析表明，模仿性同构和强制性同构可以解释对价聚集现象，而规范性同构不能解释它。由于我们的被解释变量是一个连续变量 (比率)，因此，我们通过进一步的分析表明强制性同构的影响事实上也是微弱的。这样，我们不仅利用制度理论解释了对价高度聚集的奇怪现象，而且还把制度同构理论中的三种不同的因素–已有的研究很难区分它们 – 分解开，从而推动制度同构相关研究的发展。